A rapid approach for determining the mechanical properties of geopolymer concrete based on image processing technology (IPT). (16th May 2023) - Fan, L.F.; Ding, H.; Zhong, W.L.; Xu, C.B.
Graphical abstract: Highlights: A rapid method for determining the mechanical properties of concrete was proposed. The effect of aggregate content on mechanical properties of concrete was studied. The optimal aggregate content of geopolymer concrete was determined. The peak stress increases first and then decreases as aggregate content increases. Abstract: The rapid determination of the mechanical properties of geopolymer concrete (GPC) is important for improving the efficiency of repair engineering. In this study, a rapid approach for the determination of the mechanical properties of GPC based on image processing technology (IPT) was proposed. First, a mesoscopic structure model of GPC with an aggregate content of 40.0 % was established based on IPT and the mesoscopic parameters of GPC were determined in a numerical simulation. Second, the accuracy of the mesoscopic parameters of GPC was verified by comparing the numerical simulation results and experimental results of GPC with 50.0 % aggregate content. Finally, a rapid approach combining IPT and a numerical simulation was applied to investigate the effects of aggregate contents on the mechanical properties of GPC and an optimal aggregate content was predicted. The results show that the approach based on IPT and numerical simulation can accurately predict the mechanical properties of GPC with an error of less than 10.0 %. The failure mode predicted by the approach is also consistent with the actual failure mode obtained by the experiment. The results also show that the optimum aggregate content predicted by the proposed approach is 65.0 %, which has the highest compressive strength and is consistent with the experimental results. The proposed approach has potential application prospects in rapid repair engineering, due to its non-contact, accurate and efficient characteristics.